2007
DOI: 10.1161/atvbaha.107.147009
|View full text |Cite
|
Sign up to set email alerts
|

CXCR2 Blockade Impairs Angiotensin II–Induced CC Chemokine Synthesis and Mononuclear Leukocyte Infiltration

Abstract: Objective-Angiotensin II (Ang-II) and mononuclear leukocytes are involved in atherosclerosis. This study reports the inhibition of Ang-II-induced mononuclear cell recruitment by CXCR2 antagonism and the mechanisms involved. Methods and Results-Ang-II (1 nmol/L, i.p. in rats) induced CXC and CC chemokines, followed by neutrophil and mononuclear cell recruitment. Administration of the CXCR2 antagonist, SB-517785-M, inhibited the infiltration of both neutrophils (98%) and mononuclear cells (60%). SB-517785-M had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Indeed, recent studies indicate that AngII can induce neutrophil infiltration. 22,23 In addition, AngII is also able to activate neutrophils and stimulate the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase-dependent production of reactive oxygen metabolites, which may promote the oxidative autoactivation of pro-MMP9. 48,49 In the current study, we could show the gelatinolytic metalloproteinase activity and superoxide production in the neutrophil-infiltrated dissecting aortic tissue from the BAPN/AngII-treated mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent studies indicate that AngII can induce neutrophil infiltration. 22,23 In addition, AngII is also able to activate neutrophils and stimulate the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase-dependent production of reactive oxygen metabolites, which may promote the oxidative autoactivation of pro-MMP9. 48,49 In the current study, we could show the gelatinolytic metalloproteinase activity and superoxide production in the neutrophil-infiltrated dissecting aortic tissue from the BAPN/AngII-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, AngII is known to promote neutrophil infiltration into vascular walls, 22,23 and to induce MMP9 expression in cell types such as vascular smooth muscle cells. 24 Thus, we also measured the AngII levels in serum samples of the control, nonruptured aneurysm, AMI, and AAD groups, and found that the circulating AngII level was significantly higher in the AAD and AMI groups relative to the other groups studied (Figure 1).…”
Section: Elevated Levels Of Mmp9 and Angii In Blood Samples From Aad mentioning
confidence: 99%
“…SB-517785-M (Glaxo-Smith-Kline) is an antagonist that selectively inhibits CXCR2. This agent significantly reduced angiotensin II-induced infiltration of mononuclear cells and neutrophils into rat arterioles, suggesting that it may inhibit atherogenesis by controlling recruitment of neutrophils into the vessel wall (Nabah et al 2007; Drechsler et al 2011). Treatment of Ldlr −/− mice with NBI-74330 , a CXCR3 antagonist, markedly increased the content of Tregs in atherosclerotic plaques but reduced effector T cells in lymph nodes draining the aortic arch, thus attenuating atherosclerotic lesion formation in these mice (van Wanrooij et al 2008).…”
Section: Chemokine/chemokine Receptor Antagonists In Atherogenesismentioning
confidence: 96%
“…65,111 MCP-1 is upregulated in the vessel wall of hypertensive animals by angiotensin II and mechanical stress. [112][113][114][115][116] In CCR2-deficient mice, hypertension-induced macrophage infiltration and vascular hypertrophy are significantly reduced. Similarly, mice with CCR2-deficient leukocytes display a blunted response to angiotensin II regarding vascular inflammation and aortic wall thickening 117,118 (Table 1).…”
Section: Mcp-1/ccr2 Is Important In Monocyte Homingmentioning
confidence: 99%